Immune‐Related Adverse Events in the Setting of PD‐1/L1 Inhibitor Combination Therapy. (21st November 2019) - Zubiri, Leyre; Allen, Ian M.; Taylor, Martin S.; Guidon, Amanda C.; Chen, Steven T.; Schoenfeld, Sara R.; Neilan, Tomas G.; Sise, Meghan E.; Mooradian, Meghan J.; Rubin, Krista M.; Leaf, Rebecca Karp; Parikh, Aparna R.; et al.
Abstract : In 2018, a multi‐disciplinary workshop was held at the Massachusetts General Hospital to discuss challenges in defining, diagnosing, and treating immune‐related adverse events (irAE), including those that occur in patients administered PD‐1/L1 inhibitor combination therapy. In this commentary, the workshop participants present a clinical case that illustrates the complexity of irAE diagnosis and management in a patient receiving PD‐1/L1 combination therapy, summarize the current state of PD‐1/L1 combination therapy, and discuss challenges and opportunities for the evaluation of irAEs as these combinations become more widely used to treat patients with cancer.